The potential of strigolactones to shift competitive dynamics among two Rhizophagus irregularis strains - Klein, Malin; Bisot, Corentin; Oyarte Gálvez, Loreto; Kokkoris, Vasilis; Shimizu, Thomas S.; Dong, Lemeng; Weedon, James T.; Bouwmeester, Harro; Kiers, E. Toby (Frontiers in Microbiology, 2024)
Strigolactones are phytohormones that influence arbuscular mycorrhizal fungal (AMF) spore germination, pre-symbiotic hyphal branching, and metabolic rates. Historically, strigolactone effects have been tested on single AMF strains. An open question is whether intraspecific variation in strigolactone effects and intraspecific interactions can influence AMF competition. Using the Rhizophagus irregularis strains A5 and C2, we tested for intraspecific variation in the response of germination and pre-symbiotic growth (i.e., hyphal length and branching) to the strigolactones GR24 and 5-deoxystrigol. We also tested if interactions between these strains modified their germination rates and pre-symbiotic growth. Spore germination rates were consistently high (> 90%) for C2 spores, regardless of treatment and the presence of the other strain. For A5 spores, germination was increased by strigolactone presence from approximately 30% to 70% but reduced when grown in mixed culture. When growing together, branching increased for both strains compared to monocultures. In mixed cultures, strigolactones increased the branching for both strains but led to an increase in hyphal length only for the strain A5. These strain-specific responses suggest that strigolactones may have the potential to shift competitive dynamics among AMF species with direct implications for the establishment of the AMF community.